A study on transformation of some transition metal oxides in molten steelmaking slag to magnetically susceptible compounds - Shatokha V.; Semykina A.; Nakano J.; Sridhar S.; Seetharaman S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Sustainable development of steelmaking requires solving a number of environmental problems. Economically feasible and environmentally friendly recycling of slag wastes is of special concern. Research of the team representing National Metallurgical Academy of Ukraine, Royal Institute of Technology, Carnegie Mellon University and URS Corp revealed a possibility of the controlled phase transformations in the liquid silicate melts followed by formation of the magnetically susceptible compounds. This approach enables selective recovery of metal values from slag. In this paper, the results obtained and further research directions are discussed. A possibility to exploit physical properties of the transition metals, typical for the metallurgical slags (such as Fe, Mn, V and others), and corresponding specific properties of their compounds, such as non-stoichiometry, mixed valency, pseudomorphosis, thermodynamic stability etc, in production of value-added materials from slag wastes is discussed. The results of the studies of thermodynamics and kinetics of oxidation in slags followed by phase transformation with binary, ternary and complex oxides under various physicochemical conditions are discussed in the view of their application for production of the materials with predefined physical properties. Peculiarities of precipitation in slags with various basicities are analysed and demonstrate capacity of the proposed approach in the production of the material with a given structure and size - for example, nano-sized crystals with structure of spinel. The approaches towards industrial realization of the developed method are also discussed.